2021
DOI: 10.1007/s11739-021-02714-y
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage in suspected COVID-19 cases with a negative nasopharyngeal swab: a retrospective cross-sectional study in a high-impact Northern Italy area

Abstract: COVID-19 diagnosis relies on molecular testing for SARS-CoV-2 via nasopharyngeal swab in the presence of suggestive clinical, radiological and laboratory findings. Since bronchoalveolar lavage liquid (BAL) collected during fibrobronchoscopy may increase test sensitivity compared to nasopharyngeal swabs, it was performed during the 2020 pandemic in clinically or radiologically suspected cases. Our aim was to determine whether clinical features, chest computed tomography (CT) findings or laboratory tests may pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The study of Barberi and colleagues [ 15 ] fits perfectly into this context and may provide further insights on the issue. In this retrospective analysis, 198 subjects with at least one negative NPS underwent RT-PCR on BAL to detect SARS-CoV-2.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The study of Barberi and colleagues [ 15 ] fits perfectly into this context and may provide further insights on the issue. In this retrospective analysis, 198 subjects with at least one negative NPS underwent RT-PCR on BAL to detect SARS-CoV-2.…”
mentioning
confidence: 68%
“…Identifying those patients who may benefit most from BAL testing may also be helpful to reduce unnecessary costs and ensure effective resource allocation, although limited evidence currently exists. In their analysis, the authors found some variables associated with an increased likelihood of BAL positivity, including CT characteristics [ 15 ], but these data are preliminary, and need confirmation on larger prospective cohorts. Further studies are needed to define the role of BAL, and which subgroup of suspected COVID-19 patients represents the optimal population to test with BAL.…”
mentioning
confidence: 99%
“…84 However, with growing experience and availability of adequate PPE, the experts agreed that the same diagnostic procedures can be performed in patients with COVID-19 as for other patients. [85][86][87]…”
Section: Aerosol Generating Proceduresmentioning
confidence: 99%
“…11 Barberi et al reported in a cohort of 198 patients with suspected COVID-19 and negative NP swabs, 32 (16%) patients had positive BAL. 12 But multiple case reports and studies have reported lower concordance between NP swabs and BAL. [13][14][15] Patrucco et al reported a sensitivity of NP swabs of 23% in a cohort of 43 patients, as 33 patients with negative NP swabs were subsequently diagnosed with COVID-19 on BAL.…”
Section: Open Accessmentioning
confidence: 99%